Athen, Griechenland. »Shapes of Ancient Greece«: Ein Projekt zur Digitalisierung der archäologischen Sammlung der Abteilung Athen. Der Beginn der Arbeiten 2021 - Ritter, Jonathan; Ruppenstein, Florian; Skolik, Annika; Sporn, Katja (e-Forschungsberichte des DAI, 2021)
The project »Shapes of Ancient Greece« is funded by the Federal Ministry of Education and Research and aims at digitizing and re-contextualizing the complete archaeological collection of the Athens branch of the German Archaeological Institute. Furthermore, all the approximately 37.000 objects will be provided with metadata. Most of these objects are pottery sherds. The items will be both photographed and scanned. The »Laser Aided Profiler« is used for generating two-dimensional profil drawings. The »Go!SCAN 3D-Scanner« for creating 3D models of selected objects. The digital images and the metadata will be published in iDAI.objects and linked to other databases under the umbrella of the iDAI.world portal.